Mid-Career Adult Learners in an Online Doctoral Program and the Drivers of Their Academic Self-Regulation: The Importance of Social Support and Parent Education Level - Williams, Peter E.; Wall, Natalie; Fish, Wade (International Review of Research in Open and Distributed Learning, 2019)
Adult professionals enroll in online graduate programs and rely on social support and on their ability to self-regulate to be successful. The literature on academic self-regulation among emerging adults (traditional college age) is ample, but we do not know how social support interacts with academic self-regulation among adult graduate students at mid-career, particularly among those students who are first generation college goers. This study addressed the following questions: (1) To what degree do parental education level and cohort progression predict academic self-regulation? and (2) What sources of social support – family, friends, loved one (significant other), and classmates – are predictive of academic self-regulation for adult students in an online doctoral program? Findings include evidence that the influence of parental educational level on academic self-regulation persists through midlife. Also, that perceived social support from family, friends, and peers predicts academic self-regulation. We conclude with implications for the design of online programs.